The Poetics of Aristotle and the Tractatus Coislinianus : a bibliography from about 900 till 1996 - Schrier, Omert J. (Mnemosyne, Supplements, 1998)
The bibliography of Aristotle's Poetics by Cooper and Gudeman, most welcome in 1928, has now become antiquated, even for the period it covers. The present one registers all editions, translations, commentaries and studies bearing on the Poetics or the major concepts that have been associated with it, correctly or incorrectly, from 1481 up till 1996. Moreover, a survey is given of the medieval translations and commentaries written in the Orient and in Europe. Special attention has been given to the reviews. The oldest one registered dates from 1697. The second book of the Poetics being lost, publications related to the Tractatus Coislinianus , which partly rests on Poetics II , have been included. There are seven indices. Especially those on passages and subjects should prove to be useful instruments. In the author's text Greek nouns and adjectives have been transliterated.